Modification of some denture cleaning agents employed with mechanical cleansing methods (Mustansiria Dental Journal, 2018)
The present study was carried out to investigate the effect of 5 cleaning agents(dettol soap, whitening tooth paste, sodium bicarbonate powder, and ethanol handsanitizer gel and siwak powder) on color alteration of heat-polymerized acrylic resinand to compare it with that of distilled water. 60 specimen strips of heat-polymerizedacrylic resin material were prepared measuring 5mm width, 40mm length and 2mmthickness; five specimens were used for each group. After two weeks of immersion intea solution, the light transmission percent value for each specimen was determined at400nm and 700nm wave lengths by a spectrophotometer device.Then the half of the stained specimens were cleaned by the cleaning agents bybrushing with a hand brush , and rest specimens were cleaned by the same cleaningagents by an electrical dental brush and again measure the light transmission percentvalue for each specimen by the spectrophotometer device.The result obtained in this study showed that ethanol gel specimen group has thehighest mean value for light transmission among all the specimen groups of hand andmotor brush at the two wave lengths, followed by tooth paste, siwak powder, sodiumbicarbonate powder & dettol soap groups but distal water group has the lowest one.Furthermore, there were no measurable differences between the hand brush and theelectric tooth brush with respect to staining removal from the acrylic resin specimensfor all cleaning agents groups used in this study.